A method for preparing a planar electrolyte supported SOFC
Through the method of co-firing of the cathode and anode, the viscosity and layer thickness of the anode and cathode slurry of SOFC are regulated, and the existing problems of complex sintering and high warping are solved, and the effects of simplifying the process, shortening time and improving flatness are achieved.
Patent Information
- Application Number
- CN202411823610.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-08
AI Technical Summary
During the sintering process, the existing electrolyte-supported SOFCs are complicated to prepare and have large warpage at room temperature and are prone to breaking due to inconsistent thermal expansion coefficients of the cathode and anode materials.
The flat-type electrolyte support SOFC preparation method of cathode and anode co-firing is adopted. By regulating the viscosity of the anode slurry and the thickness of the cathode layer and the anode layer, the cathode co-firing is realized, simplifying the sintering process and reducing warpage.
The sintering process is simplified, the sintering time is shortened, the warpage of the SOFC battery is reduced, and the surface flatness is improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid oxide fuel cells, and in particular relates to a method for preparing a planar electrolyte supported SOFC. Background Art
[0002] Solid oxide fuel cell (SOFC) is a highly efficient energy conversion device with an electrical efficiency of up to 55%. If cogeneration is achieved, its electrical efficiency can reach over 80%, which is higher than any traditional generator or other type of fuel cell.
[0003] Compared with other types of fuel cells, solid oxide fuel cells have a wider range of fuels to choose from. Industrial hydrogen, natural gas, city gas, methanol, alcohol, diesel and some biofuels can be directly or after simple treatment used in solid oxide fuel cell power generation systems. Therefore, solid oxide fuel cells are recognized as a bridge to a hydrogen energy society and are widely used in cogeneration power plants, engines for trains and ships, auxiliary power sources for trucks and cars, distributed power stations, etc. In addition, solid oxide fuel cells are all-ceramic structures and do not require precious metals as catalysts for electrode reactions when operating at medium and high temperatures of 650 to 900°C, thereby reducing the cost of power generation. Based on the above advantages, solid oxide fuel cells are a very promising fuel cell.
[0004] Solid oxide fuel cells are mainly composed of cathodes, anodes and electrolytes. According to the type of support, solid oxide fuel cells can be divided into three types, namely anode-supported, electrolyte-supported and cathode-supported. Among them, electrolyte-supported solid oxide fuel cells have attracted widespread attention due to their good redox resistance and thermal cycle resistance. At present, due to the inconsistency of the thermal expansion coefficients of the cathode and anode materials, most electrolyte-supported solid oxide fuel cells use a cathode and anode step-by-step sintering method, that is, first prepare the anode layer on one side of the electrolyte sheet, then sinter the anode layer, and then prepare the cathode layer on the other side of the electrolyte sheet, and then sinter the cathode layer. This step-by-step sintering process is relatively complicated, and the prepared single cell has a large warpage at room temperature and is easy to break during testing or stacking. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a planar electrolyte supported SOFC with co-firing of anode and cathode.
[0006] In a first aspect, the present invention provides a method for preparing a planar electrolyte-supported SOFC with co-fired anodes and cathodes, using the following technical scheme: A method for preparing a planar electrolyte supported SOFC with co-fired anodes and cathodes, comprising the following steps: (1) Preparing anode slurry: preparing zirconium oxide, nickel oxide, binder, dispersant and solvent into anode slurry; wherein: the viscosity of the anode slurry is 15~25cps; (2) preparing cathode slurry: preparing zirconium oxide, lanthanum strontium cobalt iron, a binder, a dispersant and a solvent into a cathode slurry; wherein: the viscosity of the cathode slurry is 95-105% of the viscosity of the anode slurry; (3) screen printing, spraying or coating the anode slurry in step (1) on one surface of the flat electrolyte support, and drying to obtain an electrolyte support containing an anode layer; screen printing, spraying or coating the cathode slurry on the other surface of the electrolyte support containing the anode layer, and drying to obtain an electrolyte support containing an anode layer and a cathode layer; wherein the thickness of the cathode layer is 95-105% of the thickness of the anode layer; (4) Sintering the electrolyte support body containing the anode layer and the cathode layer in step (3) to obtain a planar electrolyte supported SOFC.
[0007] Preferably, in step (1), the specific preparation method of the anode slurry is: dissolving the binder in a solvent to obtain a colloidal solution; dispersing zirconium oxide and nickel oxide in the solvent, then adding the colloidal solution, rolling the slurry, and then adding a dispersant thereto, stirring and mixing, and degassing to obtain the anode slurry; Preferably, in step (1), the mass ratio of zirconium oxide, nickel oxide and the total amount of solvent is (7-9):(7-9):(16-20); the mass ratio of the total mass of zirconium oxide and nickel oxide to the mass of the binder is (14-18):(0.1-2); and the mass ratio of the binder to the dispersant is (0.1-2):(0.1-2).
[0008] Preferably, in step (1), the pulping is performed 4 to 6 times, the stirring speed is 1600 to 2000 rpm, the stirring time is 20 to 40 min, and the degassing is performed by vacuum degassing, the vacuum degree is -90 to -40 KPa, and the degassing time is 5 to 15 min.
[0009] Preferably, in step (2), the specific preparation method of the cathode slurry is: dissolving the binder in a solvent to obtain a colloidal solution; dispersing zirconium oxide and lanthanum strontium cobalt iron in the solvent, then adding the colloidal solution to perform slurry rolling, and then adding a dispersant thereto, stirring and mixing, and degassing to obtain the cathode slurry.
[0010] Preferably, in step (2), the mass ratio of zirconium oxide, lanthanum strontium cobalt iron powder and the total amount of solvent is (4-6):(4-6):(16-20); the mass ratio of the total mass of zirconium oxide and lanthanum strontium cobalt iron powder to the binder is (8-12):(0.1-2); and the mass ratio of the binder to the dispersant is (0.1-2):(0.1-2).
[0011] Preferably, in step (2), the pulping is performed 2 to 4 times, the stirring speed is 1100 to 1300 rpm, the stirring time is 20 to 40 min, and the degassing is performed by vacuum degassing, the vacuum degree is -90 to -40 KPa, and the degassing time is 5 to 15 min.
[0012] Preferably, in steps (1) and (2), the solvent is one or both of ethanol and methanol; the binder is one or both of polyvinyl alcohol and methyl cellulose; and the dispersant is one or both of fish oil and sodium methacrylate.
[0013] Preferably, in step (3), the planar electrolyte support is a zirconium oxide planar electrolyte support; the thickness of the anode layer is 10-20 μm; the drying temperature is 70-90° C., and the drying time is 20-40 min.
[0014] Preferably, in step (4), the sintering temperature is 1100-1300° C.; the sintering time is 2-4 h; and the sintering heating rate is 4-6° C. / min.
[0015] Beneficial effects of the present invention: The present invention achieves co-firing of cathode and cathode electrodes by regulating the viscosity of anode slurry and cathode slurry as well as the thickness of cathode layer and anode layer, simplifies the existing sintering process, and shortens the existing sintering time; meanwhile, it also effectively reduces the warpage of SOFC cells and improves their surface flatness. DETAILED DESCRIPTION
[0016] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and carefully in combination with preferred embodiments below, but the protection scope of the present invention is not limited to the following specific embodiments. Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0017] Preparation Example 1 Preparation of a planar electrolyte support Step 1: ball milling: first add 2kg of 5mm zirconium balls, 3kg of 10mm zirconium balls, and 6kg of 15mm zirconium balls into a 50L ball mill; then add 10kg of zirconium oxide powder, 6kg of butanone, 1kg of ethanol, and 0.2kg of fish oil into the ball mill, and perform the first ball milling at a speed of 100rpm for 12h, and then add 0.5kg of polyvinyl alcohol and 0.8kg of fish oil into the ball mill, and perform the second ball milling at a speed of 100rpm for 12h to obtain ball milled slurry.
[0018] Step 2: Degassing and aging: The ball mill slurry is transferred to a 50L degassing reactor, and the degassing reactor is degassed at a pressure of -0.09Mpa. The degassing speed is 30rpm, the degassing time is 2h, and the constant temperature water bath is 25°C. After the degassing is completed, the constant temperature water bath is closed, the speed is adjusted to 20rpm, and the aging is performed for 5h to obtain the degassed slurry.
[0019] Step 3: Casting: Load the defoamed slurry into the casting machine, set the casting machine speed to 0.6m / min, the feeding height to 15mm, the scraper height to 700μm, the drying temperature of zone 1 to 30℃, the drying temperature of zone 2 to 60℃, and the drying temperature of zone 3 to 90℃; turn on the casting machine, cast the defoamed slurry and dry it into a film to obtain a cast film green body. After cutting the cast film green body, dry it in an explosion-proof oven at 120℃ for 5h to obtain a dried green body.
[0020] Step 4: debinding and sintering: stack 8 dried green sheets into a layer and place them on a ceramic refractory support plate for debinding and sintering. The debinding temperature is 400°C and the debinding time is 24 hours. After debinding, sintering is carried out at a sintering temperature of 1500°C, a sintering insulation time of 5 hours, and a sintering heating rate of 3°C / min. After sintering, a zirconia flat-plate electrolyte support is obtained.
[0021] Example 1 Step 1: Prepare anode slurry Dissolve 0.5g polyvinyl alcohol and 9g ethanol in a beaker at 60°C to obtain a colloidal solution for later use. Mix 8g zirconium oxide powder, 8g nickel oxide powder and 10g ethanol, and stir and disperse them at 1000rpm for 20min to obtain a primary slurry. Add all the colloidal solution to the primary slurry, and after rolling the slurry 4 times in a three-roll mill, add 1g fish oil to obtain a secondary slurry; stir the secondary slurry at 1800rpm for 20min, and then vacuum degas for 10min at a vacuum degree of -50Kpa to obtain an anode slurry. The viscosity of the anode slurry was measured by a viscometer to be 20.0cps.
[0022] Step 2: Prepare cathode slurry Dissolve 1.0g polyvinyl alcohol and 9g ethanol in a beaker at 60°C to obtain a colloidal solution for later use. Mix 5g zirconium oxide powder, 5g lanthanum strontium cobalt iron powder and 10g ethanol, and stir and disperse them at 800rpm for 20min to obtain a primary slurry. Add all the colloidal solution to the primary slurry, and after rolling the slurry three times in a three-roll mill, add 0.5g fish oil to obtain a secondary slurry; stir the secondary slurry at 1200rpm for 30min, and then vacuum degas for 10min at a vacuum degree of -50Kpa to obtain a cathode slurry. The viscosity of the cathode slurry was measured by a viscometer to be 20cps.
[0023] Step 3 Screen printing anode slurry and cathode slurry The anode slurry in step 1 is screen-printed on one surface of the zirconia flat-plate electrolyte support prepared in Preparation Example 1, wherein the screen-printing process parameters are: scraper speed: 50 mm / s, ink knife speed: 50 mm / s, screen printing times: 3 times, screen printing anode thickness: 15 μm; after screen printing, it is dried at 80°C for 30 minutes to obtain a zirconia flat-plate electrolyte support containing an anode layer. The cathode slurry in step 2 is screen-printed on the other surface of the zirconia flat-plate electrolyte support (the surface without the anode layer), wherein the screen-printing process parameters are: scraper speed: 50 mm / s, ink knife speed: 50 mm / s, screen printing times: 3 times, screen printing cathode thickness is 15 μm; after screen printing, it is dried at 80°C for 30 minutes to obtain an electrolyte support containing an anode layer and a cathode layer.
[0024] Step 4: Sintering The electrolyte support containing the anode layer and the cathode layer prepared in step 3 is placed in a sintering furnace, heated to 1200° C. at a heating rate of 5° C. / min, and sintered for 3 hours to obtain a planar electrolyte-supported SOFC.
[0025] Comparative Example 1 Step 1: Prepare anode slurry: prepare anode slurry in the same manner as step 1 of Example 1.
[0026] Step 2: Prepare cathode slurry: Prepare cathode slurry in the same manner as in step 2 of Example 1.
[0027] Step 3 Screen printing anode slurry The anode slurry in step 1 is screen-printed on one surface of the zirconia flat-plate electrolyte support prepared in Preparation Example 1, wherein the screen-printing process parameters are: scraper speed: 50 mm / s, ink knife speed: 50 mm / s, screen printing times: 3 times, screen printing anode thickness: 15 μm; after screen printing, it is dried at 80°C for 30 minutes to obtain a zirconia flat-plate electrolyte support containing an anode layer. The zirconia flat-plate electrolyte support containing an anode layer is placed in a sintering furnace, heated to 1200°C at a heating rate of 5°C / min, and sintered for 3 hours to obtain a sintered zirconia flat-plate electrolyte support containing an anode layer.
[0028] Step 4: Screen printing cathode slurry The cathode slurry in step 2 is screen-printed on the other surface (the surface without the anode layer) of the sintered zirconium oxide flat-plate electrolyte support containing the anode layer, wherein the screen-printing process parameters are: scraper speed: 50 mm / s, ink knife speed: 50 mm / s, screen-printing times: 3 times, and the screen-printed cathode thickness is 15 μm; after screen printing, it is dried at 80°C for 30 minutes to obtain an electrolyte support containing an anode layer and a cathode layer; the electrolyte support containing an anode layer and a cathode layer is placed in a sintering furnace, heated to 1200°C at a heating rate of 5°C / min, and sintered for 3 hours to obtain a flat-plate electrolyte supported SOFC.
[0029] Comparative Example 2 It is basically the same as Example 1, except that in step 2, the cathode slurry is prepared differently, as follows: Dissolve 0.8g polyvinyl alcohol and 9g ethanol in a beaker at 60°C to obtain a colloidal solution for later use. Mix 5g zirconium oxide powder, 5g lanthanum strontium cobalt iron powder and 10g ethanol, and stir and disperse them at 800rpm for 20min to obtain a primary slurry. Add all the colloidal solution to the primary slurry, and after rolling the slurry three times in a three-roll mill, add 0.7g fish oil to obtain a secondary slurry; stir the secondary slurry at 1000rpm for 30min, and then vacuum degas for 10min at a vacuum degree of -50 to obtain a cathode slurry. The viscosity of the cathode slurry is 18cps.
[0030] Example 2 It is basically the same as Example 1, except that in step 2, the cathode slurry is prepared differently, as follows: Dissolve 0.9g polyvinyl alcohol and 9g ethanol in a beaker at 60°C to obtain a colloidal solution for later use. Mix 5g zirconium oxide powder, 5g lanthanum strontium cobalt iron powder and 10g ethanol, and stir and disperse them at 800rpm for 20min to obtain a primary slurry. Add all the colloidal solution to the primary slurry, and after rolling the slurry three times in a three-roll mill, add 0.6g fish oil to obtain a secondary slurry; stir the secondary slurry at 1100rpm for 30min, and then vacuum degas for 10min at a vacuum degree of -50; obtain a cathode slurry with a viscosity of 19cps.
[0031] Example 3 It is basically the same as Example 1, except that in step 2, the cathode slurry is prepared differently, as follows: Dissolve 1.15g polyvinyl alcohol and 9g ethanol in a beaker at 60°C to obtain a colloidal solution for later use. Mix 5g zirconium oxide powder, 5g lanthanum strontium cobalt iron powder and 10g ethanol, and stir and disperse them at 800rpm for 20min to obtain a primary slurry. Add all the colloidal solution to the primary slurry, and after rolling the slurry three times in a three-roll mill, add 0.4g fish oil to obtain a secondary slurry; stir the secondary slurry at 1300rpm for 30min, and then vacuum degas for 20min at a vacuum degree of -50; obtain a cathode slurry with a viscosity of 21cps.
[0032] Comparative Example 3 It is basically the same as Example 1, except that in step 2, the cathode slurry is prepared differently, as follows: Dissolve 1.2g polyvinyl alcohol and 9g ethanol in a beaker at 60°C to obtain a colloidal solution for later use. Mix 5g zirconium oxide powder, 5g lanthanum strontium cobalt iron powder and 10g ethanol, and stir and disperse them at 800rpm for 20min to obtain a primary slurry. Add all the colloidal solution to the primary slurry, and after rolling the slurry three times in a three-roll mill, add 0.3g fish oil to obtain a secondary slurry; stir the secondary slurry at 1400rpm for 30min, and then vacuum degas for 20min at a vacuum degree of -50; obtain a cathode slurry with a viscosity of 22cps.
[0033] Comparative Example 4 It is basically the same as Example 1, except that in step 3, the thickness of the screen-printed cathode is 14 μm.
[0034] Comparative Example 5 It is basically the same as Example 1, except that in step 3, the thickness of the screen-printed cathode is 16 μm.
[0035] Example 4 Step 1: Prepare anode slurry Dissolve 0.75g of methyl cellulose and 9g of ethanol in a beaker at 60°C to obtain a colloidal solution for later use. Mix 7g of zirconium oxide powder, 7g of nickel oxide powder and 10g of ethanol, and stir and disperse them at 1000rpm for 20min to obtain a primary slurry. Add all the colloidal solution to the primary slurry, and after rolling the slurry in a three-roll mill for 5 times, add 0.8g of sodium methacrylate to obtain a secondary slurry; after stirring the secondary slurry at 1600rpm for 40min, vacuum degassing for 7min under a vacuum degree of -70Kpa to obtain an anode slurry. The viscosity of the anode slurry was measured by a viscometer to be 22.4cps.
[0036] Step 2: Prepare cathode slurry Dissolve 1.2g of methyl cellulose and 9g of ethanol in a beaker at 60°C to obtain a colloidal solution for later use. Mix 6g of zirconium oxide powder, 6g of lanthanum strontium cobalt iron powder and 10g of ethanol, and stir and disperse them at 800rpm for 20min to obtain a primary slurry. Add all of the colloidal solution to the primary slurry, and after rolling the slurry in a three-roll mill for 4 times, add 0.4g of sodium methacrylate to obtain a secondary slurry; after stirring the secondary slurry at 1300rpm for 20min, vacuum degassing for 7min at a vacuum degree of -70Kpa to obtain a cathode slurry. The viscosity of the cathode slurry measured by a viscometer is 21.7cps.
[0037] Step 3 Screen printing anode slurry and cathode slurry The anode slurry in step 1 is screen-printed on one surface of the zirconia flat-plate electrolyte support prepared in Preparation Example 1, wherein the screen-printing process parameters are: scraper speed: 50 mm / s, ink knife speed: 50 mm / s, screen printing times: 4 times, screen printing anode thickness: 20 μm; after screen printing, it is dried at 70°C for 40 minutes to obtain a zirconia flat-plate electrolyte support containing an anode layer. The cathode slurry in step 2 is screen-printed on the other surface of the zirconia flat-plate electrolyte support (the surface without the anode layer), wherein the screen-printing process parameters are: scraper speed: 50 mm / s, ink knife speed: 50 mm / s, screen printing times: 4 times, screen printing cathode thickness is 20 μm; after screen printing, it is dried at 70°C for 40 minutes to obtain an electrolyte support containing an anode layer and a cathode layer.
[0038] Step 4: Sintering The electrolyte support containing the anode layer and the cathode layer prepared in step 3 is placed in a sintering furnace, heated to 1100° C. at a heating rate of 4° C. / min, and sintered for 4 hours to obtain a planar electrolyte-supported SOFC.
[0039] Example 5 Step 1: Prepare anode slurry Dissolve 0.4g polyvinyl alcohol and 8g ethanol in a beaker at 60°C to obtain a colloidal solution for later use. Mix 9g zirconium oxide powder, 9g nickel oxide powder and 10g ethanol, and stir and disperse them at 1000rpm for 20min to obtain a primary slurry. Add all the colloidal solution to the primary slurry, and after rolling the slurry in a three-roll mill for 6 times, add 0.3g sodium methacrylate to obtain a secondary slurry; after stirring the secondary slurry at 2000rpm for 20min, vacuum degassing for 15min at a vacuum degree of -40Kpa to obtain an anode slurry. The viscosity of the anode slurry was measured by a viscometer to be 22.4cps.
[0040] Step 2: Prepare cathode slurry Dissolve 1.25g polyvinyl alcohol and 10g ethanol in a beaker at 60°C to obtain a colloidal solution for later use. Mix 5g zirconium oxide powder, 5g lanthanum strontium cobalt iron powder and 10g ethanol, and stir and disperse them at 800rpm for 20min to obtain a primary slurry. Add all the colloidal solution to the primary slurry, and after rolling the slurry three times in a three-roll mill, add 0.35g sodium methacrylate to obtain a secondary slurry; stir the secondary slurry at 1100rpm for 40min, and then vacuum degas for 15min under a vacuum degree of -40Kpa to obtain a cathode slurry. The viscosity of the cathode slurry was measured by a viscometer to be 21.9cps.
[0041] Step 3 Screen printing anode slurry and cathode slurry The anode slurry in step 1 is screen-printed on one surface of the zirconia flat-plate electrolyte support prepared in Preparation Example 1, wherein the screen-printing process parameters are: scraper speed: 50 mm / s, ink knife speed: 50 mm / s, screen printing times: 2 times, screen printing anode thickness: 12 μm; after screen printing, it is dried at 90°C for 20 minutes to obtain a zirconia flat-plate electrolyte support containing an anode layer. The cathode slurry in step 2 is screen-printed on the other surface of the zirconia flat-plate electrolyte support (the surface without the anode layer), wherein the screen-printing process parameters are: scraper speed: 50 mm / s, ink knife speed: 50 mm / s, screen printing times: 2 times, screen printing cathode thickness is 12 μm; after screen printing, it is dried at 90°C for 20 minutes to obtain an electrolyte support containing an anode layer and a cathode layer.
[0042] Step 4: Sintering The electrolyte support containing the anode layer and the cathode layer prepared in step 3 is placed in a sintering furnace, heated to 1300° C. at a heating rate of 6° C. / min, and sintered for 2 h to obtain a planar electrolyte-supported SOFC.
[0043] The flatness of the planar electrolyte-supported SOFC prepared in Examples 1 to 5 and Comparative Examples 1 to 5 was tested, and the specific test method was as follows: In the present invention, parallelism, verticality and warpage are tested by an image measuring instrument. The working principle of the image measuring instrument is as follows: the image measuring instrument uses surface light, contour light and coaxial light for illumination, and then captures images through a camera lens with a zoom objective lens. The images are then transmitted to a computer screen through an S terminal, and then the software commands obtain the required elements. The image generated on the display automatically measures the object to be measured, and the optical ruler is driven by the workbench to move in the X, Y and Z directions, and the multifunctional data processor performs data processing, and the measurement is completed through calculations by the software.
[0044] The test data of Examples 1 to 5 and Comparative Examples 1 to 5 are shown in Table 1: Table 1 It can be seen from the data of Example 1 and Comparative Example 1 that when the viscosity of the cathode slurry and the anode slurry are the same and the screen-printed thickness is the same, the cathode and anode are sintered separately in Comparative Example 1, and the warpage, parallelism and verticality values of the flat-plate electrolyte-supported SOFC prepared are significantly improved compared with those in Example 1.
[0045] It can be seen from the data of Examples 1 to 3 and Comparative Examples 2 and 3 that when the viscosity of the cathode slurry and the anode slurry in Comparative Examples 2 and 3 is quite different, the values of the warpage, parallelism and verticality of the planar electrolyte supported SOFC prepared by the two are significantly improved compared with Example 1. In Examples 2 to 3, the viscosity change of the cathode slurry and the anode slurry is controlled within a certain range. Although the values of the warpage, parallelism and verticality of the planar electrolyte supported SOFC are improved to a certain extent compared with Example 1, the changes are relatively small, and the SOFC still has good flatness.
[0046] It can be seen from the data of Example 1 and Comparative Examples 4 and 5 that when the screen-printed thickness of the cathode slurry in Comparative Examples 4 and 5 is significantly different from the screen-printed thickness of the anode slurry, the warpage, parallelism and verticality values of the planar electrolyte-supported SOFC prepared by both are significantly improved compared with Example 1.
[0047] In Example 4 and Example 5, the viscosity of the cathode slurry was 96.8% and 97.7% of the viscosity of the anode slurry, respectively. The warpage, parallelism and verticality values of the planar electrolyte-supported SOFC prepared by both were relatively low, indicating that the flatness of the SOFC was good.
[0048] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a planar electrolyte supported SOFC with co-fired anode and cathode, characterized in that: The following steps are involved: (1) Preparing anode slurry: preparing zirconium oxide, nickel oxide, binder, dispersant and solvent into anode slurry; wherein: the viscosity of the anode slurry is 15~25cps; (2) preparing cathode slurry: preparing zirconium oxide, lanthanum strontium cobalt iron, a binder, a dispersant and a solvent into a cathode slurry; wherein: the viscosity of the cathode slurry is 95-105% of the viscosity of the anode slurry; (3) screen printing, spraying or coating the anode slurry in step (1) on one surface of the flat electrolyte support, and drying to obtain an electrolyte support containing an anode layer; screen printing, spraying or coating the cathode slurry on the other surface of the electrolyte support containing an anode layer, and drying to obtain an electrolyte support containing an anode layer and a cathode layer; wherein the thickness of the cathode layer is 95-105% of the thickness of the anode layer; (4) Sintering the electrolyte support body containing the anode layer and the cathode layer in step (3) to obtain a planar electrolyte supported SOFC.
2. The method for preparing a planar electrolyte supported SOFC with co-fired anode and cathode according to claim 1, characterized in that: In the step (1), the specific preparation method of the anode slurry is: dissolving the binder in a solvent to obtain a colloidal solution; dispersing zirconium oxide and nickel oxide in the solvent, then adding the colloidal solution to perform slurry rolling, and then adding a dispersant thereto, stirring and mixing, and then degassing to obtain the anode slurry.
3. The method for preparing a planar electrolyte supported SOFC with co-fired anode and cathode according to claim 1 or 2, characterized in that: In the step (1), the mass ratio of zirconium oxide, nickel oxide and the total amount of solvent is (7-9):(7-9):(16-20); The mass ratio of the total mass of zirconium oxide and nickel oxide to the binder is (14-18):(0.1-2); The mass ratio of binder to dispersant is (0.1~2):(0.1~2).
4. The method for preparing a planar electrolyte supported SOFC with co-fired anode and cathode according to claim 2, characterized in that: The number of times of pulping is 4 to 6 times, and the stirring speed is 1600 to 2000 rpm; The stirring and mixing time is 20~40min; The degassing is done by vacuum degassing, the vacuum degree is -90~-40Kpa, and the degassing time is 5~15min.
5. The method for preparing a planar electrolyte supported SOFC with co-fired anode and cathode according to claim 1, characterized in that: In the step (2), the specific preparation method of the cathode slurry is: dissolving the binder in a solvent to obtain a colloidal solution; dispersing zirconium oxide and lanthanum strontium cobalt iron in the solvent, then adding the colloidal solution to perform slurry rolling, and then adding a dispersant thereto, stirring and mixing, and degassing to obtain the cathode slurry.
6. The method for preparing a planar electrolyte supported SOFC with co-fired anode and cathode according to claim 1 or 5, characterized in that: In the step (2), the mass ratio of zirconium oxide, lanthanum strontium cobalt iron powder and the total amount of solvent is (4-6):(4-6):(16-20); The mass ratio of the total mass of zirconium oxide and lanthanum strontium cobalt iron to the binder is (8~12):(0.1~2); The mass ratio of binder to dispersant is (0.1~2):(0.1~2).
7. The method for preparing a planar electrolyte supported SOFC with co-fired anode and cathode according to claim 1 or 5, characterized in that: In the step (2), the pulping is performed 2 to 4 times; The stirring speed is 1100~1300rpm, and the stirring time is 20~40min; The degassing is done by vacuum degassing, the vacuum degree is -90~-40Kpa, and the degassing time is 5~15min.
8. The method for preparing a planar electrolyte supported SOFC with co-fired anode and cathode according to claim 1, characterized in that: In the steps (1) and (2), the solvent is one or both of ethanol and methanol; The binder is one or both of polyvinyl alcohol and methyl cellulose; The dispersant is one or both of fish oil and sodium methacrylate.
9. The method for preparing a planar electrolyte supported SOFC with co-fired anode and cathode according to claim 1, characterized in that: In the step (3), the planar electrolyte support is a zirconium oxide planar electrolyte support; the thickness of the anode layer is 10-20 μm; the drying temperature is 70-90° C., and the drying time is 20-40 min.
10. The method for preparing a planar electrolyte supported SOFC with co-fired anode and cathode according to claim 1, characterized in that: In the step (4), the sintering temperature is 1100-1300° C.; the sintering time is 2-4 hours; and the sintering heating rate is 4-6° C. / min.